Possibilities of buses on alternative fuel in public urban transport in Belgrade - Petrović, Jelica; Ivković, Ivan; Vujačić, Ivan; Žeželj, Srećko (Technological and Economic Development of Economy, 2009)
The accelerated development of transport and transport technology is significantly contributing to air pollution by motor vehicle emissions in large urban environments. The analysis of mass public transport in Belgrade, the transportation supply, the transport services delivered, the number of passengers transported, clearly concludes that by investing in its capacity, significant progress in the preservation of the city environment can be achieved. The paper analyzes the economic and environmental aspects of the modernization and renewal of the public bus subsystem as the major bearer of the transport supply through the use of alternative fuels, natural gas and biodiesel. Viešojo transporto alternatyvaus kuro taikymo galimybės Belgrade Santrauka. Didėjantys transporto ir transporto technologijų vystymosi tempai gerokai padidina oro užterštumą urbanizuotose teritorijose. Analizuojama viešojo transporto (autobusų) modernizacijos bei atkūrimo, naudojant alternatyvų kurą (natūralias dujas ir biodyzeliną), galimybe ekonominiais ir aplinkosaugos aspektais. Reikšminiai žodžiai: autobusas, natūralios dujos, biodyzelis, viešasis transportas, aplinkosauga. First published online: 21 Oct 2010